Development of JOMO Board Game Media in Group Guidance to Reduce FoMO among High School Students - Rista, Tia Fadila; Cahyaningrum, Vesti Dwi; Afriliyanto, Agus (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This research is motivated by the high tendency of Fear of Missing Out (FoMO) in students, as well as the lack of game-based media that specifically helps students reflect on FoMO in the context of daily life. A range of interventions to reduce FoMO have been developed, but most still focus on informative approaches and have not optimally encouraged active engagement and deep reflection of students in the context of real-life experiences. This research aims to develop counseling guidance media in the form of JOMO board games and test its feasibility. This research uses a Research and Development approach based on the Borg & Gall model up to the product revision stage II. The participants consisted of three media experts, three counseling subject matter experts, three prospective product users (school counselors), and eight students in a small group trial. Data was collected through questionnaires, interviews, and observations, and analyzed using the Percentage of Agreement technique. The validation results showed that the JOMO board game achieved a feasibility score of 91.07% from media experts, 90.47% from material experts, and 91.27% from potential users, all of which were categorized as very feasible. A preliminary field testing involving eight students resulted in an average response score of 89.84% in the excellent category. This media is considered interesting, easy to use, and relevant to students’ experiences, and is able to facilitate the process of reflection on FoMO. These findings indicate that the media is feasible and shows potential in facilitating students’ engagement and reflection on the FoMO phenomenon. This research is limited to the development stage and has not tested its effectiveness empirically